Discrimination of muscle and neuronal Na-channel subtypes by binding competition between [3H]saxitoxin and mu-conotoxins. - Moczydlowski, E (1986)
The effect of two mu-conotoxin peptides on the specific binding of [3H]saxitoxin was examined in isolated plasma membranes of various excitable tissues. mu-Conotoxins GIIIA and GIIIB inhibit [3H]saxitoxin binding in Electrophorus electric organ membranes with similar KdS of approximately equal to 50 X 10(-9) M in a manner consistent with direct competition for a common binding site. GIIIA and GIIIB similarly compete with the majority (80-95%) of [3H]saxitoxin binding sites in rat skeletal muscle with KdS of approximately 25 and approximately 140 X 10(-9) M, respectively. However, the high-affinity saxitoxin sites in lobster axons, rat brain, and rat heart are virtually insensitive to GIIIA concentrations up to 10 microM. These results and previously published data suggest that three Na-channel subtypes can be distinguished on the basis of toxin pharmacology: Na channels of skeletal muscle and Electrophorus electroplax have high affinity for mu-conotoxins and tetrodotoxin, neuronal Na channels have low affinity for mu-conotoxins and high affinity for tetrodotoxin, while heart Na channels and a similar subtype also found in denervated muscle have low affinity for both mu-conotoxin and tetrodotoxin.